PERAMALAN JUMLAH RUMAH TIDAK LAYAK HUNI (RTLH) GUNA MENGATASI KEMISKINAN DI DAERAH ISTIMEWA YOGYAKARTA - Arzeti Fadhila Prabasari; Cici Jesica; Farah Kurnia Arsandha; Nisa Kusumawati (Pusat Riset dan Inovasi Nasional, 2023)
Indonesia is a developing country that still has many social problems. The problem that arises in this case is the inability of the community to have a home as a comfortable place to live. At its peak in 2003 there was a backlog (inability to provide housing) of 5.93 million housing units. The purpose of this analysis is to predict the number of uninhabitable houses (RTLH) to overcome poverty in the Special Region of Yogyakarta using the Arima model. The data used is secondary data in the form of uninhabitable house data in the Special Province of Yogyakarta from 2009 to 2023. The method used is a quantitative method in the form of forecasting tests on the ARIMA (Autoregressive Integrated Moving Average) model with the help of Eviews 12 software. The results of the analysis state that in the next 10 years the number of uninhabitable houses will tend to decrease significantly so that in 2033 there will still be 85 uninhabitable housing units and will be able to become the basis for overcoming poverty in the Province of the Special Region of Yogyakarta.